2001
DOI: 10.1584/jpestics.26.55
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Insecticidal and Nerve Activities of an Imidacloprid-related Nitromethylene Compound and Its <i>N</i>-Alkyl Congeners

Abstract: An imidacloprid-related nitromethylene compound and its alkyl congeners at the imidazolidine NH site were prepared and their insecticidal and nerve-excitatory and -blocking activities were measured. In the insecticidal test with the male adult American cockroach by the injection method, metabolic inhibitors, more or less, increased the activity of tested compounds. The NH mother compound was the most active among the nitromethylene compounds and was as active as imidacloprid under the synergistic conditions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(80 citation statements)
references
References 2 publications
8
72
0
Order By: Relevance
“…Yamamoto et al demonstrated that 3N-methyl imidacloprid (15, RϭMe) was partly demethylated in vitro by a mixed function oxidase system. 36) In experiments with 3N-alkyl/allyl-imidacloprid and the nitromethylene analogues, 37,38) the introduction of these groups lowered the activity of the mother insecticides by more than 10 times in the injection test of the housefly (Musca domestica) (evaluated 1 hr after injection) and for the American cockroach (evaluated 24 hr after injection). On the other hand, in the measurement 4 days after the active ingredient was sprayed on rice plants, the 90% lethal dose of n-propyl, allyl and propargyl imidacloprid derivatives for green rice leafhoppers was as low as 0.32 ppm, comparable with that of the mother compound.…”
Section: Alkylaminesmentioning
confidence: 99%
“…Yamamoto et al demonstrated that 3N-methyl imidacloprid (15, RϭMe) was partly demethylated in vitro by a mixed function oxidase system. 36) In experiments with 3N-alkyl/allyl-imidacloprid and the nitromethylene analogues, 37,38) the introduction of these groups lowered the activity of the mother insecticides by more than 10 times in the injection test of the housefly (Musca domestica) (evaluated 1 hr after injection) and for the American cockroach (evaluated 24 hr after injection). On the other hand, in the measurement 4 days after the active ingredient was sprayed on rice plants, the 90% lethal dose of n-propyl, allyl and propargyl imidacloprid derivatives for green rice leafhoppers was as low as 0.32 ppm, comparable with that of the mother compound.…”
Section: Alkylaminesmentioning
confidence: 99%
“…NIA16388 (propargyl propyl benzenephosphonate; NIA), an inhibitor of the hydrolytic metabolism of a pyrethroid, tetramethrin, 12) was the same sample used in previous studies. [7][8][9][10] …”
Section: Biological Assaysmentioning
confidence: 99%
“…[7][8][9][10] In short, various volumes (1-10 ml) of the methanol solution of each compound containing some amount of dimethyl sulfoxide (DMSO) were injected into the abdomen of the cockroach unless otherwise noted. Organic solvents alone in this range did not show any toxic effect.…”
Section: Insecticidal Tests Against American Cockroachesmentioning
confidence: 99%
See 2 more Smart Citations